Optimization of the flotation process for the recovery of a gold pre-concentrate in sulphide minerals - Suca, Juan; Palomino, Gregorio (Technological Innovations Journal, 2022)
The objective of this research was to optimize the recovery of a gold pre-concentrate from the sulphide minerals in the flotation process, determining the parameters of percentage of solids, dosage of reagents and flotation time. of tests according to a statistical experimental design the 23-factorial design for 3 factors or variables at two levels, with 11 runs, including 3 central points, for the performance of each of the experiments. During the procedure, a sulphide mineral containing pyrite (FeS2), chalcopyrite (FeCuS2), blende or sphalerite (ZnS), galena (PbS) has been worked on. With an average grade of head (gold) of 10g/MT. For the grinding stage, the mineral has been ground to a granulometry of 65% -200 mesh. Therefore, it was also determined that the optimal grinding time for 65% -200 mesh is 21.65 minutes. It is concluded that it is possible to optimize the flotation process with a recovery of 76.96% compared to what is worked in the plant with a recovery of 70.08%, the test that has given the best results is test No. obtain a grade of 58.45 g/MT of gold in the concentrate and 2.59 g/MT of gold in the tailings; and a recovery of 76.96% of gold, in turn to obtain this recovery the solid % is 35%, collector A-238 of 50g/MT, flotation time 10 minutes. It has been determined that the most important variables that affect the process are: % of solids and dosage of the Aerofloat-238 collector.
Keywords: concentrate; flotation; gold; optimization; sulphide ore